Applications of Epipelic Diatoms and Probiotics for Pacific White Shrimp Nursery (Litopenaeus vannamei) - Wardi Wardi; Sinar Pagi Sektiana; Bambang Suprakto (Jurnal Perikanan Universitas Gadjah Mada, 2023)
Pacific white shrimp (Litopennaeus vannamei) is a type of shrimp that is very easy to cultivate because it has several advantages, it is resistant to disease and has a high survival rate, and productivity can reach 13.6 tons/ha. Very high density because it can use feed and space more efficiently. This is what makes many farmers in Indonesia cultivate it. Despite the many advantages, there are still many obstacles faced by cultivators who experience failure and losses. The failure was caused by poor water quality during cuture and the emergence of disease attacks that caused slow growth decreased production and resulted in huge losses for farmers. To overcome these problems, it is necessary to improve the water quality of the cultivation media used. Water quality improvement was carried out by the application of probiotics for the vannamei nursery. The purpose of this study was to evaluate the optimal dose/cell count on water quality and shrimp growth and evaluate the developmental level of pathogenic bacteria treated with Epipelic Diatoms (DE) and Probiotic. The method used was an experimental method using a completely randomized design (CRD) with 4 treatments and 3 replications. The treatments tested were A (pure seawater), B (100% DE), C (100% PB), D (100% DE+100% PB). The seeds used were PL 6 vannamei shrimp with an average weight of 0.175 g and an average length of 5.5. The results showed that the combination of DE and PB had a significant effect (p<0.05) on water quality and the growth and survival of post-vannamei larvae.